2020
DOI: 10.1063/1.5135696
|View full text |Cite
|
Sign up to set email alerts
|

Parameter-free coordination numbers for solutions and interfaces

Abstract: Coordination numbers are among the central quantities to describe the local environment of atoms and are thus used in various applications such as structure analysis, fingerprints and parameters. Yet, there is no consensus regarding a practical algorithm, and many proposed methods are designed for specific systems. In this work, we propose a scale-free and parameter-free algorithm for nearest neighbor identification. This algorithm extends the powerful Solid-Angle based Nearest-Neighbor (SANN) framework to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Having established the "universal" character of the nonadditivity interaction, we now focus on the case of Pt(111) to obtain a geometric understanding of its origin. Since the structures are essentially two-dimensional, we do not simply determine the coordination number, 55 but perform a directional analysis: in each structure, the H-bond (H• • • O distance below 2.5 Å) acceptors are identified. Then, they are classified according to the Pt-O distance (<3.0 Å for chemisorbed water molecules, > 3.0 Å for physisorbed molecules).…”
Section: Ctmentioning
confidence: 99%
“…Having established the "universal" character of the nonadditivity interaction, we now focus on the case of Pt(111) to obtain a geometric understanding of its origin. Since the structures are essentially two-dimensional, we do not simply determine the coordination number, 55 but perform a directional analysis: in each structure, the H-bond (H• • • O distance below 2.5 Å) acceptors are identified. Then, they are classified according to the Pt-O distance (<3.0 Å for chemisorbed water molecules, > 3.0 Å for physisorbed molecules).…”
Section: Ctmentioning
confidence: 99%
“…Furthermore, we have shown that the solvation shell of cations indeed fluctuate significantly, and cation specifically, at the electrified interface. 183 For electrocatalytic reactions, where both the electrolyte and the adsorbate have to rearrange, the situation is less clear: During the reaction, the adsorbate undergoes a bond-breaking/formation process (horizontal axis of Figure 5) and the electrolyte (vertical axis) has to adapt to the new arrangement. If the solvent rearrangement is fast (flat solvation free energy surface in y-direction) compared to the nuclear reorganization, then the adiabatic approximation applied to the stationary states can also be applied to the transition state (TS) and no special treatment is necessary.…”
Section: The Rise and Fall Of Implicit Solventsmentioning
confidence: 99%
“…Hence, we enable the use of DockOnSurf for adsorption sites that differ in orientation. For every adsorption site, a normal vector to the surface is either provided by the user, or, more conveniently, automatically determined using the Anisotropically corrected Solid-Angle based Nearest-Neighbors (ASANN) 63 algorithm.…”
Section: Screeningmentioning
confidence: 99%
“…The generalized coordination numbers of their surface atoms ranged from 1.6-5, making it an ideal test-case, as already observed in our previous study on coordination numbers. 63 For the identification of adsorption modes on corrugated surfaces, we chose a 3×3 supercell of the (0001) facet of hematite in its Fe-O 3 -Fe-termination when hydrated by one dissociated water molecule per unit cell. 68 Its lowest four atomic layers were kept frozen in its bulk arrangement.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation